International human resource management - Brewster, Chris; Houldsworth, Elizabeth; Sparrow, Paul; Vernon, Guy (Chartered Institute of Personnel and Development, 2016)
International Human Resource Management is a critically engaging and student friendly textbook for International HRM modules at all levels, including the CIPD Level 7 Advanced International HRM module. Providing wide international coverage and incorporating a global strategy perspective, it offers a particular focus on cross-cultural, comparative and strategic HRM issues, with a strong emphasis on culture and its impact on organizational behaviour and HRM. This fully updated 4th edition of International Human Resource Management includes extended coverage of cross-cultural management, a broader scope of countries and key topics such as global talent management, global leadership, global knowledge management, and differing national contexts. Filled with geographically diverse examples and case studies, and covering topics from culture and reward systems to managing expatriate assignment and diversity in international forms of working, it is an ideal textbook for all students of international HRM as well as HRM specialists and practicing managers. Online supporting resources include an instructor's manual, lecture slides and additional case studies.